Evaluation and assessment of clinical and demographic profile, aetiology and outcome of status epilepticus in paediatric patients - Garasiya, Nirav Z.; Patel, Priyanshi P. (International Journal of Contemporary Pediatrics, 2023)
Background: Status epilepticus (SE) is one of the most frequent neurological emergencies that require prompt diagnosis and treatment. If not managed promptly, it may result in significant neurological morbidity and mortality. Methods: It is prospective observational study. Study for clinical and demographic profile, aetiology, outcome in patient of status epilepticus. Results: Occurrence of SE is in indoor paediatric patients was 2.05%. Male and female M: F ratio is 1.3:1. Fever was common associated symptoms in SE. The commonest type of seizure was generalised tonic-clonic seizure (GTCS). Infective etiology was most common amongst patients with SE. secondary epilepsy with CP was second most common cause followed by complex febrile seizure and primary epilepsy. In infants, metabolic etiology was the most common cause for SE. Majority of seizures were controlled only by benzodiazepines. Requirement of midazolam infusion was only in few patients and requirement of anesthetic agent was rare. Mechanical ventilation was frequently required in patients with refractory status epilepticus (RSE) and super-refractory status epilepticus (SRSE). Mortality was almost same in all age groups with SE. Mortality was directly proportional to duration of the SE and was highest in patient having >30 minutes of duration of seizure. Conclusions: SE was more commonly associated with male gender and age <5 years. By improving hygiene, nutritional and vaccination status, overcrowding and education, we can reduce occurrence of SE, by reducing infections. Mortality can be reduced by immediate control of seizure and improving intensive care facilities.